Persepsi Risiko Pengelola Hotel Kecil dan Menengah di Kabupaten Sleman, Yogyakarta terhadap Dampak COVID-19 - Sari Nastiti Nurrachma Iqbal (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2020)
COVID-19 has been declared a global pandemic by the World Health Organization (WHO). The rapid and uncontrollable transmission of COVID-19 has a significant impact on the tourism industry. The hotel occupancy rate in Yogyakarta’s Sleman Regency has dropped dramatically to an average of 10%. The majority of the hotels in Sleman Regency, Yogyakarta that are affected by COVID-19 are small and medium-sized. The purpose of this study is to investigate the risk perceptions of small and medium-sized hotel managers regarding the impact of COVID-19 and their response to it. This study employs a qualitative approach, conducting in-depth interviews with three small and medium-sized hotel managers in Sleman Regency, Yogyakarta, via online video conferencing or video calls. This study finds that each hotel manager’s risk perception differs, which influences decision-making in responding to danger. Hotel managers’ risk perception is also useful for developing risk communication skills in hotel employees. The study’s findings also suggest that implementing a health protocol in each hotel to reduce the risk of COVID-19 could provide hotel managers with peace of min.